2020
DOI: 10.1155/2020/6410614
|View full text |Cite
|
Sign up to set email alerts
|

Gas Transport in Shale Nanopores with Miscible Zone

Abstract: Based on the results of molecular dynamics simulation, in a gas-water miscible zone, the velocity profiles of the flowing water film do not increase monotonously but increase first and then decrease, which is due to the interaction between water and gas molecules. This exhibits a new physical mechanism. In this paper, we firstly propose a gas-water flow model that takes into account the new physical phenomena and describes the distribution of gas-water velocity in the whole pore more accurately. In this model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The effect of pressure on the flow process will be investigated in future work. Therefore, the driving force of gas flow comes from a gas concentration difference between the liq-layer and the vac-layer in our simulations rather than a external force and a pressure difference …”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of pressure on the flow process will be investigated in future work. Therefore, the driving force of gas flow comes from a gas concentration difference between the liq-layer and the vac-layer in our simulations rather than a external force and a pressure difference …”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation has been extensively applied to understand the dynamics behaviors of gas molecules on the nanoscale. , MD simulations can provide the information on the gas transport characteristic within nanopores taking into account the radical ambient conditions (e.g., high pressure and low temperature). , In previous studies, the different gas–water two-phase flow models in the hydrophobic nanopore or the hydrophilic nanopore had been constructed by MD simulation. Also, the effects of pore surface properties, water concentration, and the gas–water two-phase velocity on the two-phase flow behaviors were reported. The flows of these MD simulations were driven by an external force. Zhang et al reported the two-phase flow process of CH 4 –H 2 O in a silica nanopore by a new method “nanomanometer” using MD simulation.…”
Section: Introductionmentioning
confidence: 99%
“…As conventional resources worldwide continue to deplete gradually, tight oil, with its significant resource potential, has emerged as a focal point for global development. , During the water displacement process, a thin, bound water film typically develops on the rock surface. , The issue of water films formed by bound water was first raised in the 1950s . It has been demonstrated that the bound water film thickness within the pore space is generally uniform and consistent, typically ranging from 0.01 to 0.1 μm, and occupies a significant portion of the pore volume . Bound water films are important for shale, tight, and low-permeability reservoirs .…”
Section: Introductionmentioning
confidence: 99%